Fatty acid suppression of glial activation prevents central neuropathic pain after spinal cord injury. Issue 12 (December 2019) - Georgieva, Marieta; Wei, Yuting; Dumitrascuta, Maria; Pertwee, Roger; Finnerup, Nanna B.; Huang, Wenlong
Abstract : Abstract: About half of patients with spinal cord injury (SCI) develop debilitating central neuropathic pain (CNP), with no effective treatments. Thus, effective, safe, and novel therapies are needed urgently. Previously, docosahexaenoic acid (DHA) was reported to confer neuroprotection in preclinical SCI models. However, its therapeutic potential on SCI-CNP remains to be elucidated. Here, we demonstrated for the first time that intravenous DHA administrations with 3-day intervals (250 nmol/kg; starting 30 minutes after injury and maintained for 6 weeks) effectively prevented SCI-CNP development in a clinically relevant rat contusion model. SCI-CNP was assessed by a novel sensory profiling approach combining evoked pain measures and pain-related ethologically relevant rodent behaviours (burrowing, thigmotaxis, and place/escape avoidance) to mimic those for measuring human (sensory, affective, cognitive, and spontaneous) pain. Strikingly, already established SCI-CNP could be abolished partially by similar DHA administrations, starting from the beginning of week 4 after injury and maintained for 4 weeks. At spinal (epicenter and L5 dorsal horns) and supraspinal (anterior cingulate cortex) levels, both treatment regimens potently suppressed microglial and astrocyte activation, which underpins SCI-CNP pathogenesis. Spinal microgliosis, a known hallmark associated with neuropathic pain behaviours, was reduced by DHA treatments. Finally, we revealed novel potential roles of peroxisome proliferator–activated and retinoid X receptors and docosahexaenoyl ethanolamide (DHA's metabolite) in mediating DHA's effects on microglial activation. Our findings, coupled with the excellent long-term clinical safety of DHA even in surgical and critically ill patients, suggest that systemic DHA treatment is a translatable, effective, safe, and novel approach for preventing and managing SCI-CNP. Abstract : Supplemental Digital Content is Available in the Text.Systemic treatments with docosahexaenoic acid prevent central pain development after spinal injury and partially abolish already established central pain at a chronic stage of injury.